Optical Heisenberg ferromagnetic model for directional inextensible flows of spacelike curves with geometric phase - Körpınar, Talat (Scientific Publishers, 2019)
In this paper, we introduce the notion of the Heisenberg ferromagnetic model for directional inextensible flows of spacelike curves by using the quasi-frame in the Minkowski space. Furthermore, we study some integrability conditions for quasi-frame fields. With this new concept, we derive the necessary and sufficient condition for the given curve to be the inextensible flow. Finally, we give some new characterizations for quasi-curvatures of the spacelike curve by Heisenberg ferromagnetic model and we obtain total phase for quasi-vector fields. © 2019, Indian Association for the Cultivation of Science.
Keywords: 02.40.?k; 03.50.De; 04.20.?q; Curvatures; Geometric phase; Heisenberg ferromagnetic model; Inextensible flows; Quasi-frame